Metabolic and performance adaptations to interval training in endurance-trained cyclists - Westgarth-Taylor, Ch.; Hawley, J. A.; Rickard, S.; Myburgh, K. H.; Noakes, T. D. (European Journal of Applied Physiology, 1997)
This study examined the effects of sustained high-intensity interval training (HIT) on the athletic performances and fuel utilisation of eight male endurance-trained cyclists.